Effect of π-linkers in Triphenylamine-EDOT based dye sensitizers for DSSCs: A DFT approach - Pooja Kundu; Prabhakar Chetti (Chemical Physics Impact)
In this study, organic molecules with various π-linkers having triphenylamine (TPA) donor core and 3,4-ethylenedioxythiophene (EDOT) as internal acceptor in conjugation with cyanoacrylic acid (CAA) anchoring group on the photovoltaic performance were systematically investigated. The charge transportability, stability, and optical characteristics was estimated using density functional theory (DFT) technique. The molecules exhibited wide absorption spectra ranges 370–480 nm with a noticeable trend towards longer wavelengths, accompanied by low excitation energies. The HOMO (H), LUMO (L), HOMO-LUMO energy gap (∆Eg), ionization potential (IP), electron affinity (EA), reorganization energy are assisted for consideration of suitable energy levels for charge transfer, electron injection, dye regeneration. The impact of π-linkers on the efficacy of DSSCs was determined by scrutinizing necessary photovoltaic parameters like JSC, ΔGreg, ΔGinj, LHE, VOC, DOS and power conversion efficiency. The dye (NH) with pyrrole π-linker influences the absorption energies for achieving high-efficiency (7.49 %) for solar cell and provide valuable insights into the configuration relationship of organic sensitizers. These findings highlight the potential of reported dye molecules that can exhibit enhanced electronic characteristics has broadened possibilities for the optimization of their photovoltaic properties and are better sensitizers for the assembly of dye sensitized solar cells (DSSCs).